Improving Students’ Writing Ability by Using Student Teams Achievement Divisions (STAD) Method - Juhelmi, Juhelmi; Hasan, Hasan (Maspul Journal of English Studies, 2021)
The aims of this research is to find out how Student Teams-Achievement Divisions (STAD) can improve students’ descriptive writing ability of the eighth grade students at Mts Darul Falah Islamic Boarding School, Enrekang in the 2018/2019 academic year. The research employed a quasi experimental. This research used the experimental class and the control class. Class VIII A as an experimental class and class VIII B as a control class. The experimental class consisted of 30 students and the control class consisted of 30 students. The instrument used in this study was writing descriptive papers about classmates and family. The results of the study showed that there was an improvement in students writing ability between pre-test and post-test in the experimental class after treatment. Before conducting the treatment, the value obtained is t0 = 1.570 < tt = 2.001 which shows that it does not have a significant effect in improving students' writing ability after being test using t-test result, but after being given treatment and post-test values t0 = 4.336 > tt = 2.001 with a significance level of a = 0.05 and df n₁+ n₂ -2 = 58 then t0 is higher than tt which shows a significant influence in improving students' writing ability using the STAD method. In the experimental class was used STAD method and the control class was used the conventional method and the final average score of students in the experimental class is 72.80 > 59.83. The values above indicate that the use of the STAD method significantly improving students writing ability in write descriptive texts